Duration of anticoagulation after venous thromboembolism in real world clinical practice. Issue 4 (April 2015) - Ageno, Walter; Samperiz, Angel; Caballero, Ruth; Dentali, Francesco; Di Micco, Pierpaolo; Prandoni, Paolo; Becattini, Cecilia; Uresandi, Fernando; Verhamme, Peter; Monreal, Manuel; ,
Abstract: Introduction: Venous thromboembolism (VTE) carries a considerable risk of recurrence and anticoagulants should be administered for a minimum of three months. Since little is known about real life management of VTE, we aimed to describe current practice in the secondary prevention of VTE. Materials and Methods: Using the database of an international, prospective registry on patients treated for VTE, RIETE, information was collected on risk factors for VTE and bleeding, anticoagulant treatment, and clinical outcomes during follow up. Multivariate analysis using logistic regression was performed to identify predictors of treatment duration. Results: Of 6944 patients with a first episode of VTE 41.1% had unprovoked VTE, 31.8% had transient risk factors, 27.1% had cancer. After the exclusion of patients who died during the first year of observation, the rate of patients treated for > 12 months was 55.1%, 41.9%, and 43.2%, respectively (p < 0.001). Pulmonary embolism at presentation, recurrence while on treatment, chronic heart failure and age > 65 years were independently associated with treatment for > 12 months. Body weight < 75 kg, anemia, cancer, and the presence of transient risk factors were associated with treatment for 12 months or less. Major bleeding occurred more frequently than recurrent VTE in patients with VTE secondary to transient risk factors and cancer; fatal bleeding was more frequent than fatal recurrent PE in all subgroups. Conclusions: We observed heterogeneous duration of anticoagulant treatment for the secondary prevention of VTE. A substantial proportion of patients, in particular those with VTE secondary to transient risk factors, may be exposed to a possibly unnecessary risk of bleeding. Highlights: A substantial proportion of VTE patients receives anticoagulants for > 1 year. Fatal bleeding events outweigh fatal pulmonary embolism. The majority of fatal bleeds occur after the first 3 months of treatment.